Kajian Lafaz Ditinjau dari Segi Kejelasan Maknanya (Lafaz Zahir, Nash, Mufassar dan Muhkam) - W, Wawan; Ami, Abd. Rauf Muhammad; F, Fatmawati (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The study of wording in usul al-fiqh occupies a very important position in understanding the texts of the Qur'an and hadith, because it is from here that Islamic law is derived. Among the main topics of discussion is the analysis of wording in terms of its meaning, particularly the categories of zahir, nash, mufassar, and muhkam. These four categories play a strategic role in the process of istinbath (derivation) of law, as they determine the level of clarity, the possibility of interpretation, and the finality of a text. This study uses a qualitative approach with a literature review method, examining classical and contemporary literature, both usul al-fiqh books and modern studies. The results of the study show that: (1) zahir wording is clear but still open to interpretation, (2) nash wording is more definitive and can only be interpreted according to its primary meaning, (3) mufassar is very clear wording that does not require additional interpretation, and (4) muhkam is the most definitive wording that does not accept changes in meaning. This study confirms that the hierarchy of the meaning of lafaz is an important tool in maintaining the balance between preserving the authority of the text and the need for contextualization of Islamic law. Thus, this classification remains relevant in addressing contemporary Islamic legal issues.